Immunogenicity of biologic therapies in psoriasis: Myths, facts and a suggested approach. (1st January 2021) - Tsakok, T.; Rispens, T.; Spuls, P.; Nast, A.; Smith, C.; Reich, K.
Abstract: With biologic drugs dominating the therapeutic space for severe immune‐mediated inflammatory disease, it is critical for clinicians to be familiar with the concept of drug immunogenicity, with the potential for our patients to develop antidrug antibodies (ADA) of clinical relevance. Whilst there are clear differences between different therapeutic biologics in terms of reported ADA rates, there is no accepted dermatology guideline or grouping of drugs by risk of clinically relevant ADA, nor a consensus on approach to ADA management. This is partly because making valid comparisons of immunogenicity across drugs is fundamentally flawed: the differing types of ADA assay, trial design and included patient population – as well as the molecular structure of the biologic molecules themselves – are all highly influential on reported ADA prevalence and impact on clinical response. Therefore, the first part of this article aims to give an overview of ADA that also clarifies common misconceptions on the subject, whilst the second part of this article outlines Phase III immunogenicity data on commonly used biologics for psoriasis, the most common dermatological indication. Based on this, and acknowledging current limitations in available evidence, we propose a working categorization of biologics together with a broad approach to management: Group 1 – biologics with higher risk of clinically relevant ADA; Group 2 – biologics with lower risk of clinically relevant ADA; and Group 3 – biologics with no established risk of clinically relevant ADA. However, these groupings represent a working concept only; more research is required, using comparable ADA assays and consistent reporting of related outcomes. Finally, there is an urgent need for better characterization of individuals at particular risk of developing ADA to inform future clinical decision‐making.